Three Dimensional Imaging of Ventilation Dynamics in Asthmatics Using Multi-echo Projection Acquisition with Constrained Reconstruction - Holmes, James H. (2009)
The purpose of this work is to detect dynamic gas trapping in 3-dimensions during forced exhalation at isotropic high spatial resolution and high temporal resolution using hyperpolarized helium-3 (HPHe-3) MRI. Ten subjects underwent HPHe-3 MRI and MDCT. MRI was performed throughout inspiration, breath-hold, and forced expiration. A multi-echo 3D projection acquisition was used to improve data collection efficiency and an iterative constrained reconstruction (I-HYPR) was implemented to improve SNR and increase robustness to motion. Two radiologists evaluated the dynamic MRI and breath-held MDCT data for gas and air trapping respectively. Phantom studies showed the proposed technique significantly improved depiction of moving objects compared to view-sharing methods. Gas trapping was detected using MRI in 5 of the 6 asthmatic subjects who displayed air trapping with MDCT. Locations in disagreement were found to represent small to moderate regions of air trapping. The proposed technique provides whole lung 3D imaging of respiration dynamics at high spatial and temporal resolution and compares well to the current standard, MDCT. While MDCT can provide information about static regional air trapping, it is unable to depict dynamics in a setting more comparable to a spirometry maneuver and explore the longitudinal time evolution of the trapped regions.